The Characteristics of 50 Hospitalized COVID-19 Patients With and Without ARDS - Dreher, Michael; Kersten, Alexander; Bickenbach, Johannes; Balfanz, Paul; Hartmann, Bojan; Cornelissen, Christian; Daher, Ayham; Stöhr, Robert; Kleines, Michael; Lemmen, Sebastian W; Brokmann, Jörg Christian; Müller, Tobias; et al. (Deutsches Ärzteblatt international, 2020)
The type of pneumonia (coronavirus disease 2019, COVID-19) that is caused by the new coronavirus (severe acute respiratory syndrome coronavirus 2, SARS-CoV-2) is now spreading across the world in a pandemic. Many patients with COVID-19 were admitted to the University Hospital Aachen during an outbreak that first struck the Heinsberg district in February 2020. A comparative presentation of the clinical features of the first 50 COVID-19 patients with and without acute respiratory distress syndrome (ARDS) who were hospitalized in the University Hospital Aachen. 24 intubated patients were treated in the intensive care unit for ARDS of varying degrees of severity, while 26 patients who were breathing spontaneously without ARDS, but nevertheless needed supplemental oxygen, were treated in a separate isolation ward. The median age of the patients was 65 (IQR 58-76). The median latency from symptom onset to hospitalization was four days (IQR 1-8). Patients with ARDS had preexisting respiratory diseases more commonly than patients without ARDS (58% [95% confidence interval: 39; 76] versus 42% [26; 61]) and were more commonly overweight or obese (83% [64; 93] versus 42% [26; 61]). The two groups did not differ in viral burden but displayed significant differences in laboratory findings: ARDS patients had persistently elevated values for leukocytes, interleukin-6, lactate dehydrogenase, creatine kinase, and D-dimers over the period of observation. Patients without ARDS had persistently elevated inflammatory parameters and fever for at least one week, with an accompanying need for supplemental oxygen. Three of the patients with ARDS died of multiorgan failure, while four in the non-ARDS group died of respiratory insufficiency. This initial description of a cohort of COVID-19 patients with and without ARDS in Germany reveals that those with ARDS more commonly have preexisting respiratory diseases and obesity, as well as persistently elevated inflammatory markers. COVID-19 patients without ARDS may likewise require prolonged hospitalization because of persistently elevated inflammatory values with a simultaneous need for supplemental oxygen.